6+4r=2(r-4)

Simple and best practice solution for 6+4r=2(r-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6+4r=2(r-4) equation:


Simplifying
6 + 4r = 2(r + -4)

Reorder the terms:
6 + 4r = 2(-4 + r)
6 + 4r = (-4 * 2 + r * 2)
6 + 4r = (-8 + 2r)

Solving
6 + 4r = -8 + 2r

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '-2r' to each side of the equation.
6 + 4r + -2r = -8 + 2r + -2r

Combine like terms: 4r + -2r = 2r
6 + 2r = -8 + 2r + -2r

Combine like terms: 2r + -2r = 0
6 + 2r = -8 + 0
6 + 2r = -8

Add '-6' to each side of the equation.
6 + -6 + 2r = -8 + -6

Combine like terms: 6 + -6 = 0
0 + 2r = -8 + -6
2r = -8 + -6

Combine like terms: -8 + -6 = -14
2r = -14

Divide each side by '2'.
r = -7

Simplifying
r = -7

See similar equations:

| 4h-42=-18 | | -10.1=w+.3 | | 5x-3=2x+26 | | 7w+3w=40 | | 7r^2+91r+280=0 | | 23=13+2a | | 200+2x=4x+400 | | 9b-36=0 | | -7x-14y=14 | | -2(5-3x)-6(2x-4)=x+1 | | -12+4t=0 | | 3(5x+39)=(X+26) | | -2x+17=x+8 | | 25=25+9r | | v=25(30) | | -2x+17=8+x | | -12r-48=12 | | -(5-3x)-6(2x-4)=x+1 | | 24x^4=36x^3-12x^2/12x^2 | | 19+3c=40 | | 7log(4x-1)=14 | | 5b-5.25b+3=3.75 | | -4c+5=9 | | -12x^2/12x^2 | | 3y+6=6-5x | | -6n-8=10 | | 7ln(4x-1)=14 | | 7+5d=42 | | (3x-40)+(2x+11)=180 | | tan(59)=.125/x | | 2(x+3)5=9 | | 11p=144 |

Equations solver categories